Emerging techniques in 'truly' minimal-invasive treatment options of benign prostatic obstruction. Issue 3 (May 2017) - Sievert, Karl-Dietrich; Kunit, Thomas
Abstract : Purpose of review: Benign prostatic enlargement is a common age-related condition, affecting over 50% of men aged more than 60 years. Side effects of medical therapy and significant morbidity of transurethral resection of the prostate and open surgery led to the development of so-called minimally invasive procedures, with the aim to be efficient but with less morbidity and shorter or no hospitalization. For this review, a systematic literature was performed. We report recent results in different treatment options for benign prostate hypoplasia (BPH) and recommend the best minimal-invasive treatment for BPH. Recent findings: Within recent years, BPH surgical interventions underwent a shift. Although standard techniques have further improved because of new products and increased business competition, there has been a request from healthcare administration to reduce costs and inpatient treatment. As important, the patients understanding of outcome, fast relief, and recovery might change the common urological outcome measurement. The two main aspects are quality of life and sexuality. Summary: Some of the presented treatments are already established in EAU guidelines, others may be recognized in clinical practice as a suitable alternative treatment to transurethral resection of the prostate and medical therapy. Patients now wish to be more involved in the treatment option decision-making and seem very concerned about side effects and their return to normal life. However, variations in reimbursements allowed in different countries can affect the treatment option.